HUBUNGAN MANAJEMEN NUTRISI IBU MENYUSUI TERHADAP PENINGKATAN PRODUKSI ASI DI WILAYAH KERJA PUSKESMAS MONCONGLOE KABUPATEN MAROS - Trisinarti; Amriati Mutmainna; Jamila Kasim (STIKES Nani Hasanuddin, 2022)
Breast milk is one of the sources of life for children which is very important because it is a natural food ingredient that can be given by a mother to her child after birth at the beginning of his life. Good nutrition for breastfeeding mothers is important because it can increase milk production. According to WHO data (2016), between 2007 and 2014, the global coverage of exclusive breastfeeding was only around 36%. Meanwhile, one of the 2015 Sustainable Development Goals (SDGs) is exclusive breastfeeding at least 80% of breastfeeding mothers give breast milk to their babies. The purpose of this study was to determine the relationship between nutrition management for breastfeeding mothers and increased milk production in the working area of ​​the Moncongloe Public Health Center, Maros Regency. This research uses quantitative research with survey method with cross sectional design. Sampling using accidential sampling technique, obtained 54 respondents. Data was collected using a questionnaire leaflet and analyzed by Chi-Scuare test (p < 0.05). The results of the analysis showed that there was a relationship between Nutrition Management of Breastfeeding Mothers and Increased Breast Milk Production which was indicated by the results of the Chi-Square statistical test, p value = 0.003. The conclusion of this study is that there is a relationship between Nutrition Management of Breastfeeding Mothers on Increasing Breast Milk Production in the Working Area of ​​the Moncongloe Public Health Center, Maros Regency.